Transaortic Cannulation for Balloon Pumping in a Patient with Angina and Abdominal Aortic Occlusion - Yoshida, Kazunori; Tobe, Satoshi; Yamaguchi, Masahiro (Japanese Journal of Cardiovascular Surgery, 2006)
A 64-year-old man with a history of abdominal aortic occlusion was admitted because of anterior chest pain. Angina pectoris with ischemic mitral regurgitation were diagnosed by transthoracic echocardiography and coronary artery angiography. He underwent coronary artery bypass grafting and mitral valve annuloplasty with a 26-mm Physio-ring. Because of difficulty in weaning from cardiopulmonary bypass, he required IABP support which was introduced via the ascending aorta. On the 2nd postoperative day, IABP was discontinued and the sternum was closed. His postoperative course thereafter was uneventful without any neurological complications. Postoperative echocardiogram showed good mitral valve function. He was discharged 16 days after surgery.